Law and legacy in medical jurisprudence : essays in honour of Graeme Laurie - Dove, E. S. (Edward S.); Nic Shuibhne, Niamh; Laurie, G. T. (Graeme T.) (Cambridge : Cambridge University Press, 2022)
Graeme Laurie stepped down from the Chair in Medical Jurisprudence at the University of Edinburgh in 2019. This edited collection pays tribute to his extraordinary contributions to the field. Graeme often spoke about the importance of 'legacy' in academic work and forged a remarkable intellectual legacy of his own, notably through his work on genetic privacy, human tissue and information governance, and the regulatory salience of the concept of liminality. The essays in this volume animate the concept of legacy to analyse the study and practice of medical jurisprudence. In this light, legacy reveals characteristics of both benefit and burden, as both an encumbrance to and facilitator of the development of law, policy and regulation. The contributions reconcile the ideas of legacy and responsiveness and show that both dimensions are critical to achieve and sustain the health of medical jurisprudence itself as a dynamic, interdisciplinary and policy-engaged field of thinking.
Doing medical law and ethics : putting interdisciplinarity to work / Sharon Cowan, Emily Postan, and Nayha Sethi -- A philosopher looks at 'law and medical ethics' / Richard Ashcroft -- Thinking outside the box : Graeme Laurie's legacy to medical jurisprudence / Roger Brownsword -- The public interest in health research : from concept to context / Annie Sorbie -- Taking the legacy of liminality forward : reflections on Graeme Laurie's approach to liminality and its relevance for the ethics and governance of reproduction / Catriona McMillan and Agomoni Ganguli-Mitra -- The once and future importance of impact / Eric M. Meslin -- Breathing life into law : what it means to take an ethics + approach to conceptualise law in research governance / Calvin Ho and Justin Wong --Biomedical research policy : back to the future? / Bartha Maria Knoppers, Ruth Chadwick, and Michael Beauvais -- The burden of history : how past scandals have shaped the future governance of human tissue, and health data / Nils Hoppe and José Miola -- Body parts and baleful stars? / Margaret Brazier and Alexandra Mullock -- The legacy of the Warnock Report / Emily Jackson -- Escape from the medically assisted suicide spiral / Murray Earle -- Integrating the biological and the technological : time to move beyond law's binaries? / Muireann Quigley and Laura Downey -- UK Biobank and the legal regulation of genetic research : preserving the legacy and empowering future regulation / Jean McHale -- Overcoming the regulatory impasse in stem cell research and advanced therapy medicines in Argentina through shared norms and values / Fabiana Arzuaga -- Institutions, interpretive communities, and legacy in decision-making : a case study of patents, morality, and biotechnological inventions / Aisling McMahon -- Towards a new privacy : informed consent as an encumbrance to group interests? / Mark Taylor and David Townend -- A tale of two legacies : drawing on humanist interpretations to animate the right to the benefits of science / Shawn Harmon.
Title from publisher's bibliographic system (viewed on 23 Dec 2021).
Keywords: Laurie, G. T; Medical laws and legislation; Human chromosome abnormalities -- Diagnosis -- Moral and ethical aspects; Medical ethics; Medical genetics -- Law and legislation